Co-coagulation of micro-nano bubbles (MNBs) for enhanced drinking water treatment: A study on the efficiency and mechanism of a novel cleaning process. (1st November 2022) - Lu, Jinsuo; Huang, Xiaojiang; Zhang, Zhiqiang; Pang, Heliang; Chen, Kunyu; Xia, Haozhe; Sui, Yiyu; Chen, Rongwen; Zhao, Ziang
Highlights: MNBs-coagulation process as a novel cleaning process is proposed for enhanced drinking water treatment. The involvement of MNBs in the coagulation process can force PACl hydrolysis. The involvement of MNBs in the coagulation process can increase the complexation strength of PACl with HA. The MNBs-coagulation process has great engineering implications. Abstract: MNBs (Micro-nano bubbles) are widely used in cleaning processes for environmental treatments, but few studies have examined the interaction of MNBs with coagulation. In this study, a novel process, i.e., MNBs-coagulation, was developed for enhanced drinking water treatment. The humic acid (HA) removal efficiency was used to evaluate the effectiveness of MNBs-coagulation for drinking water treatment. The hydrolysis component ratio of polymeric aluminum chloride (PACl) with and without MNBs, the complexation strength of HA and PACl, and flocculent functional group characterization were used to analyze the mechanism of the MNBs-coagulation process to enhance drinking water treatment. The results of a Jar test showed that the MNBs-coagulation process could improve the removal efficiency of HA (up to a 27.9% increase in DOC removal). In continuous-flow experiments to remove HA, MNBs-coagulation can increase the removal efficiency of UV254 by about 26.5% and with no significant change in turbidity. These results are attributed to the inherent hydroxyl radical generating properties of MNBs, the forced hydrolysis of PACl by MNBs to increase the Alc percentage, and the ability of MNBs to increase the complexation strength of HA with PACl. At the same time, the MNBs-coagulation process has a strong anti-interference ability, almost no interference from anions and cations such as Cl −, SO4 2− and Ca 2+, and has a good performance in natural surface water. In summary, MNBs-coagulation has strong potential for practical applications to enhance the efficiency of drinking water treatment. Graphical abstract: Image, graphical abstract